EVALUASI MANAJEMEN STRATEGIK SMK NEGERI 1 PURWOJATI DALAM MENGHADAPI PROGRAM SEKOLAH GRATIS - Rahmad Rismawan; Enjang Burhanudin Yusuf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the strategic management of SMK Negeri 1 Purwojati in implementing the free school program. This research uses a qualitative approach with data collection through interviews and observations with school management, teachers, and students. The results show that SMK Negeri 1 Purwojati has effectively implemented strategic management in facing the free school program. The school has employed various strategies, including planning, pattern, position, perspective, and tactics, to achieve the program's objectives. The findings also indicate that the school has successfully increased access to education for underprivileged communities and improved the quality of educational services. This study provides several recommendations to enhance the quality of education and access to education for underprivileged communities.